Effectiveness of Using YouTube Video-Based Science Learning Media on Class VIII Student Learning Outcomes - Atyka Trianisa; Tri Putri Wahyuni (Science Journal Get Press, 2024)
Natural science education (IPA) is an integral part of the education curriculum that aims to introduce students to scientific concepts, develop problem-solving skills, and improve their understanding of natural phenomena. The use of YouTube video-based science learning media has great potential in improving the effectiveness of science learning. By stimulating student engagement, strengthening visual understanding, providing accessibility and flexibility, and increasing learning motivation, YouTube video-based science learning media can be a powerful tool in achieving better learning outcomes at the secondary education level. This research uses a quantitative research approach. This type of research uses Quasi-experimental Design research. Quasi experimental Design, while the research design is Non equivalent Control Group Design. that there is a difference in learning outcomes between the control class and the experimental class with a significant value of 0.021 <0.05 which means H0 is rejected and H1 is accepted. The results of this study concluded that there was an effect of using Youtube video-based science learning media on the learning outcomes of 8th grade students. Continue to integrate the use of YouTube videos in teaching methods and always carry out regular monitoring and evaluation of the impact to ensure that learning objectives are achieved optimally.